Identification and characterization of the 285L and K145R proteins of African swine fever virus. (30th July 2019) - Hübner, Alexandra; Keßler, Catharina; Pannhorst, Katrin; Forth, Jan Hendrik; Kabuuka, Tonny; Karger, Axel; Mettenleiter, Thomas C.; Fuchs, Walter
Abstract : African swine fever (ASF) is a lethal disease of domestic pigs and wild boar, against which no vaccines are available to date. The large dsDNA genome of African swine fever virus (ASFV) contains up to 167 ORFs predicted to encode proteins. The functions and antigenic properties of many of these proteins are still unknown, which impedes vaccine development. Based on the results of mass spectrometry-based proteome analyses of ASFV-infected cells, two highly abundant but previously uncharacterized viral proteins, p285L and pK145R, were investigated in detail. To this end, monospecific rabbit antisera and corresponding gene deletion mutants of ASFV were prepared. RNA and immunoblot analyses revealed that p285L is an early gene product expressed prior to viral DNA replication, whereas pK145R is a true late protein. The predicted membrane protein p285L could be localized in purified ASFV particles. In contrast, pK145R was not detectable in virions, but accumulated diffusely in the cytoplasm of infected cells. Deletion of 285L or K145R from the genome of a virulent ASFV strain from Armenia did not significantly affect spread and productive growth in a permissive wild boar lung cell line, nor in primary macrophage cultures. Future studies must elucidate, whether p285L and pK145R, although non-essential for in vitro propagation of ASFV, are relevant for replication or virulence in swine. Furthermore, it remains to be investigated whether deletion of the abundant ASFV proteins p285L or pK145R might support serological differentiation from wild-type-infected animals.